Neuropathic pain after spinal cord injury and physical exercise in animal models: A systematic review and meta-analysis. (January 2020) - Palandi, Juliete; Bobinski, Franciane; de Oliveira, Gabriela Martins; Ilha, Jocemar
Highlights: Mechanical and thermal nociception are the most frequently assessed NP components. Physical exercise shown beneficial effect on mechanical, thermal and cold nociception, and spontaneous pain. The benefits of physical exercise vary according to its starting and total duration. There is a large heterogeneity about the type and intensity of exercise to alleviating NP after SCI. Abstract: The aim of this systematic review was to summarize the effects of physical exercise on neuropathic pain (NP) in animal models of SCI. The search was conducted in Medline and Science Direct to identify experimental preclinical studies involving animal models of SCI, physical exercise as an intervention and the assessment of NP. Fifteen articles met the eligibility criteria. The review shows that in studies of NP involving animal models of SCI, rodents are the most common species. Thoracic contusion is the most common injury and mechanical and thermal nociception are the most frequently assessed NP components. The benefits of physical exercise vary according to its starting period and total duration. In addition, there is considerable heterogeneity regarding the type and intensity of exercise capable of alleviating NP after SCI. Furthermore, physical exercise has beneficial effects on mechanical, thermal and cold nociception, and spontaneous pain. These results are weakened by the paucity of studies involving these pain outcomes. The review protocol is published for free access on the SyRF platform (http://syrf.org.uk/protocols/ ).